Mechanical and Physical Properties of Kelempayan (Neolamarckia Cadamba) Particleboard - W.M, Nazri; Sakinah M.T, Nur; K, Jamalu (International Journal of Engineering and Technology, 2018)
The aim of this study was to investigate the role of the particle size, board density, resin content and hot press temperature on the properties of particleboard composite. Single-layered Kelempayan (Neolamarckia cadamba) particleboards bonded with phenol formaldehyde (PF) resins were manufactured. The boards were fabricated with three different particle sizes (0.5, 1.0 and 2.0 mm), two different board densities (600 and 700 kgm-3), two different resin contents (9 and 11%) and two different hot press temperatures (155 and 165ËšC). The boards produced were evaluated for their modulus of elasticity (MOE), modulus of rupture (MOR), internal bond (IB) and thickness swelling (TS) in accordance with the Malaysia Standards. The study revealed that boards from smaller particles, higher resin contents and higher hot press temperatures gave higher MOE, MOR, IB and improved the TS. However, boards with higher densities gave higher MOE, MOR, IB and TS. Overall, the boards with the particle size of 0.5 mm, board density of 700 kgm-3, resin content of 11% and 165ËšC of hot press temperature exhibited the greatest performance and were able to fulfill the Malaysia Standard specifications for furniture grade used in dry (PF1) and humid (PF2) and also for load-bearing applications in dry (PS1).Â Â